ANALISIS FAKTOR-FAKTOR YANG DIPERTIMBANGKAN SISWA DALAM PENGAMBILAN KEPUTUSAN SEKOLAH DI SMK NASIONAL MOJOSARI - M. Syamsul Hidayat; Eny Setyariningsih (Bisman (Bisnis dan Manajemen): The Journal of Business and Management, 2020)
The purpose of this study was to determine what factors influenced students choosing schools at the National Vocational School in Mojosari. With the limitation of the problem in this study, the students who attend the Mojosari National Vocational Schools in grades 2 and 3. Vocational High Schools (Vocational High Schools) are a formal educational institution that organizes vocational education from secondary/junior high school. The method in this research uses quantitative methods. The population in this study was all students in grade 2 and 3 who attended the National Vocational School in Mojosari. To determine the sample using an opinion (Maholtra, 2006:291) that is 4 or 5 times the number of variables known in this study the variables are 42 x 4 = 168, so the number of samples from this study amounted to 168 respondents. The technique used is proportionate stratified random sampling, this technique is used for populations that have proportional and non-homogeneous stratified members/elements (Sugiyono, 2016:82). Sources of data in this study are primary, secondary and documentation data. For the results of factor analysis, the KMO (Kaisser-Meyer-Olkin) measure of sampling adequacy of 0.706 is greater than 0.5 and there are 42 variables whose values are above 0.5. For the factors formed there are 15 factors out of 42 variables. Of the 15 factors formed, the most influential were school product factors with a variance value of 15,885.